Integrasi Nilai Budaya Jawa Dalam Strategi Konseling Multibudaya Untuk Mengembangkan Sikap Peserta Didik - Sri Harsantik, Gatis; Khusumadewi, Ari (Universitas Palangka Raya, 2026)
Cultural diversity in Indonesia demands an inclusive and adaptive educational approach, including guidance and counseling services. Multicultural counseling is an essential strategy to help students understand, appreciate, and interact harmoniously with individuals from different cultural backgrounds. This study aims to analyze the integration of Javanese cultural values into multicultural counseling strategies to strengthen students’ tolerance attitudes. The research employed a library study method using content analysis of books, scientific articles, and relevant previous studies. The findings reveal five core Javanese cultural values rukun (harmony), tepa selira (empathy), gotong royong (cooperation), sabar and eling (self-control and awareness), and adil (justice) which have significant potential to enhance the effectiveness of counseling services, particularly in resolving student conflicts. The study also identifies three multicultural counseling training models Multicultural Action Project (MAP), KIPAS, and Hypothetical that can be adapted to strengthen counselors’ multicultural competence. In conclusion, integrating Javanese cultural values into multicultural counseling can foster an inclusive and character-oriented school environment while enhancing counselors’ capacity to deliver culturally responsive services.